2005
DOI: 10.1007/s00125-005-1772-9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary-fat-induced obesity in mice results in beta cell hyperplasia but not increased insulin release: evidence for specificity of impaired beta cell adaptation

Abstract: Long-term fat feeding is associated with an increase in the beta cell population but an inadequate functional adaptation. Thus, a functional rather than a morphological abnormality appears to underlie dietary-fat-induced beta cell dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(119 citation statements)
references
References 59 publications
8
106
2
Order By: Relevance
“…We have previously reported that mice overexpressing MCH manifest islet hyperplasia (18). To evaluate whether the converse effect, i.e., loss of MCH, leads to reduced ␤-cell mass, we examined MCH-KO mice under two conditions known to independently influence islet growth: genetic background (36,37) and high-fat feeding (38). Effect of genetic background on alterations in ␤-cell mass in MCH-KO mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that mice overexpressing MCH manifest islet hyperplasia (18). To evaluate whether the converse effect, i.e., loss of MCH, leads to reduced ␤-cell mass, we examined MCH-KO mice under two conditions known to independently influence islet growth: genetic background (36,37) and high-fat feeding (38). Effect of genetic background on alterations in ␤-cell mass in MCH-KO mice.…”
Section: Resultsmentioning
confidence: 99%
“…Most mouse models of obesity exhibit an islet compensatory response to maintain euglycemia in the face of insulin resistance (rev. in 37,38). To begin to dissect the dynamic effects of MCH on modulating ␤-cell mass, we fed MCH-KO mice and their wild-type littermates with a high-fat diet/ hypercaloric diet for 16 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…This notion is supported by the general observation that type 2 diabetes mellitus does not develop in most obese individuals or in pregnant women, who can have severe insulin resistance [3,7,8], due to a compensatory process involving increased beta cell function and notably beta cell mass expansion [3,[9][10][11].…”
Section: Introductionmentioning
confidence: 84%
“…Several mechanisms could underlie the expansion of ␤-cells in this setting. First, ␤-cell replication can be driven by increased secretory demand placed upon the islet by dietary-fat-induced obesity and insulin resistance or chronic, mild hyperglycemia (24,25). Additionally, secreted factors such as hepatocyte growth factor or glucagon-like peptide-1 can induce ␤-cell replication (26 -28).…”
Section: Discussionmentioning
confidence: 99%